2019
DOI: 10.1111/eje.12421
|View full text |Cite
|
Sign up to set email alerts
|

Moving the four habits model into dentistry. Development of a dental consultation model: Do dentists need an additional habit?

Abstract: A consultation model for dentistry is presented, with communication skills in a didactic and structural format, applicable for most types of visits, patients and problems. A characteristic of the dental visit is its division into dialogue phases and clinical phases, which makes verbal exchange especially challenging. The original Four Habits Model (4H) has been adapted from medicine to the specific structure and content of a dental visit, and a modified model is proposed. The dental model consists of a structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…This is a space in which the dental practitioner has created a predictable environment that allows the patient to gain a stronger sense of control. A previous study investigating dentistry consultation models found that creating predictability and establishing a safe space affected the therapeutic alliance, which likely positively influences practitionerpatient collaboration and interaction [52]. A safe space is also considered essential to facilitating dental attendance for abuse survivors and children with dental anxiety [12,53].…”
Section: Discussionmentioning
confidence: 99%
“…This is a space in which the dental practitioner has created a predictable environment that allows the patient to gain a stronger sense of control. A previous study investigating dentistry consultation models found that creating predictability and establishing a safe space affected the therapeutic alliance, which likely positively influences practitionerpatient collaboration and interaction [52]. A safe space is also considered essential to facilitating dental attendance for abuse survivors and children with dental anxiety [12,53].…”
Section: Discussionmentioning
confidence: 99%
“…The model has produced favourable outcomes in Norwegian hospitals [23]. It has been adapted to dentistry and is today an essential part of the dental curriculum at the University of Oslo [24,25]. This model comprises four main elements, for didactic reasons called habits, which involve the communication skills and behaviours of the health professional.…”
Section: Introductionmentioning
confidence: 99%
“…Sociolinguists Coleman and Burton [18] originally pointed out that there is considerable difference between dental and medical consultations in that the latter are hands-on treatment sessions only in exceptional cases. This has also been echoed recently in the dental literature [13,19,20]. The functions of the physician in a typical consultation are to investigate symptoms and patient perceptions, aid diagnosis, prescribe treatment, review progress and give information and advice.…”
Section: Special Characteristics About the Dental Clinic And Communic...mentioning
confidence: 94%
“…The functions of the physician in a typical consultation are to investigate symptoms and patient perceptions, aid diagnosis, prescribe treatment, review progress and give information and advice. The structure as described by sociolinguist Long and others [20,21] is a sequence of phases, which closely resemble other decisionmaking schemes in other disciplines: (1) greeting the patient; (2) discovering the patient's reasons for attending; (3) conducting a physical or verbal examination (or both); (4) sharing information with the patient; (5) detailing further courses of action (i.e., prescription of drugs or referral); and (6) closing the consultation. More recently, it has evolved towards patient-centered communication and is called the "six-functions model" as reviewed by King and Hoppe [11]: (1) fostering the relationship, (2) gathering information, (3) providing information, (4) making decisions, (5) responding to emotions, and (6) enabling disease-and treatment-related behavior in closure.…”
Section: Special Characteristics About the Dental Clinic And Communic...mentioning
confidence: 99%